2009
DOI: 10.3113/fai.2009.1048
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Painful Plantar Callosity after Hallux Valgus Correction without Lesser Metatarsal Osteotomy

Abstract: Painful plantar callosities under the lesser metatarsals in patients with hallux valgus deformity can be improved by hallux valgus correction alone without lesser metatarsal osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Our results showed that females had a higher incidence rate of HV, and the percentage of female patients was 87.0%, 96.0%, 95.9%, and 94% from group 1 to group 4, respectively. ere was no significant different in this rate between groups, which is consistent with the gender distribution of HV patients in the literature [6,20,21] (Table 1).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results showed that females had a higher incidence rate of HV, and the percentage of female patients was 87.0%, 96.0%, 95.9%, and 94% from group 1 to group 4, respectively. ere was no significant different in this rate between groups, which is consistent with the gender distribution of HV patients in the literature [6,20,21] (Table 1).…”
Section: Discussionsupporting
confidence: 90%
“…e main reason for this pain is that the medial ligamentous tension is weakened in early HV patients. With increasing severity in the degree of HV deformity, the phalanx slowly drifts into a valgus position and the metatarsal head escapes from the sesamoid platform [6]. e medial articular cartilage on the first metatarsal head thus loses the normal contact relation with the proximal phalanx and is no longer subjected to the normal pressure [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations